Implementasi Media Pembelajaran Berbasis Game Monopoli Dalam Pembelajaran Akuntansi Untuk Meningkatkan Kemampuan Berpikir - Anggraini, Tiara Putri; Syofyan, Rita (Jurnal Ecogen, 2025)
The low critical thinking ability of students is indicated by the results of the odd semester summative assessment, which shows that conventional learning media has not been effective in developing students' critical thinking skills. To overcome this problem, learning media is needed that makes students active in the learning process in order to improve students' thinking skills. One of the learning methods that actively involves students in the learning process is the monopoly game learning media. This research seeks to develop students critical thinking skills through the integration of monopoly game media in the learning process. The study was conducted at SMK Negeri 3 Padang with the research subjects of class XI Accounting students. This research is a quantitative research with a quasi-experimental research type (quasi-experimental design) with a Pretest-Posttest Control Group Design. The research sample was selected using purposive sampling. The research instrument used was HOTS-based learning outcome test questions. The hypothesis in this study was examined through a paired sample t-test. Based on the analysis of post-test data from both the experimental and control groups at a 5% sig. level, the obtained Sig. (2-tailed) value was 0.000, which is less than 0.05. Therefore, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. The increase can be seen from the average Pre-Test score and the average Post-Test score in the experimental group increasing from 55.00 to 80.00. While in the control group it decreased from 60.00 to 58.00 (p <0.05). Based on the t-test testing criteria, it can be concluded that there is an influence of monopoly game learning media on students' critical thinking skills in accounting. This shows that the application of monopoly game learning media significantly improves students' critical thinking skills compared to conventional learning media. Thus, it can be concluded that monopoly game-based learning media is effective in optimizing students' high-level thinking skills.